Development and Utilization of a Modified Resonator Tube Apparatus for Sound Wave Experiments - Bello, Alwielland Q. (JPAIR Multidisciplinary Research, 2013)
Acoustic resonance is a physical phenomenon in which in-phase sound wavcombine together to produce maximum amplitude; on the other hand, out-of-phase sound waves cancel each other to produce minimum amplitude. The purpose of this study is to investigate and demonstrate this phenomenon with the use of a reliable device. This study requires a modified resonator tube apparatus to be developed and fabricated from locally-available materials for the purpose of demonstrating resonance and normal modes of sound waves. Air column length versus harmonic number (L vs n) and frequency versus harmonic number (f vs n) experiments were performed together with open-pipe and stopped-pipe procedures.
Keywords: Physics; Sound Waves; Resonance; Normal Modes; ExperimentalMethod; Philippines